Optimization and accuracy of faecal pellet count estimates of population size: The case of European rabbits in extensive breeding nuclei. (May 2016) - Rouco, C.; Santoro, S.; Delibes-Mateos, M.; Villafuerte, R.
Highlights: Improving cost-efficiency of abundance indices are crucial for species management. We determined the minimum sampling effort based on wild rabbit faecal pellet counts. We provided an R function suitable to optimize estimation of count data indexes. Abstract: Cost-effective indices to estimate relative abundances of species are crucial for their management and conservation. As an example, population indices are needed to monitor extensive breeding nuclei used for translocating wild rabbit populations. Based on counts of faecal pellets from four high density rabbit nuclei in southwest Spain: (i) we assess the accuracy of this population index in high-density populations; and (ii) present a simulation approach to evaluate how the reduction of the counting effort affects accuracy of the population estimates. Our findings suggest that this method provides a valid estimate in high-density rabbit populations, and, notably, estimates would have not substantially changed after a reduction of 45–65% in the number of counted plots depending on variation on rabbit density between nuclei. We provide a framework that managers and other scientists could use to improve data collection of pellet counts in order to optimize their chances of detecting relative abundance estimates of rabbits. In addition, we present a R function to implement our approach that can easily be applied in a variety of monitoring programmes for other species based on count data. This will likely help to reduce field-effort in different studies without compromising population indices estimates.